Upaya Meningkatkan Hasil Belajar IPA melalui Metode Demonstrasi pada Materi Siklus Air di Kelas V Sekolah Dasar - Leni Budiarti; Trikinasih Handayani; Pramudya Cahyandaru; Dewi Partini (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2022)
Abstract Education has an important role in developing the potential of a student. For this reason, innovation is needed in improving learning. This study aims to find out the steps for applying the demonstration method and student learning outcomes in science learning the material for the water cycle stages of class V SD Negeri Sidarum in 2021/2022. The research was carried out in class V, which consisted of 19 students, consisting of 8 male students and 11 female students. The design used in this study was classroom action research (CAR) using two cycles, each cycle consisting of two meetings. Methods of data collection using observation and tests. The instruments used in this study were student activity observation sheets and student learning outcomes assessment sheets. The data obtained were analyzed using qualitative and descriptive quantitative analysis. The demonstration method can improve science learning outcomes about the water cycle in fifth grade students of SD Negeri Sidarum in the 2021/2022 academic year, this can be proven by research results showing that the passing rate of student learning outcomes has increased from 75% to 89.48%. Based on the analysis and discussion of the research, it can be concluded that the demonstration method can improve student learning outcomes in science learning about water cycle material in class V SD Negeri Sidarum for the academic year 2021/2022. Keywords: Demonstration Method, Learning Outcomes, Science